2016
DOI: 10.1017/s0025315415002106
|View full text |Cite
|
Sign up to set email alerts
|

The marine biodiscovery pipeline and ocean medicines of tomorrow

Abstract: Marine organisms possess the capacity to produce a variety of unique and biologically potent natural products for treating human diseases, many of which are currently commercially available or are in advanced clinical trials. Here we provide a short review on progress in the field and discuss a case study of an EU-funded project, PharmaSea, which aims to discover novel products for the treatment of infections, inflammation and neurodegenerative diseases. Research in this sector is opening new doors for harness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 33 publications
0
85
0
Order By: Relevance
“…The marine environment is an exceptional source of both biological and chemical diversity, still largely unknown, although it has been exploited since ancient times. It has been estimated that 25% of the total number of species on Earth come from the marine environment . The uniqueness of this hostile environment in terms of light, salinity, pressure, space, gave birth to original organisms and bioactive substances, many of which exhibit characteristics not found in the terrestrial environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine environment is an exceptional source of both biological and chemical diversity, still largely unknown, although it has been exploited since ancient times. It has been estimated that 25% of the total number of species on Earth come from the marine environment . The uniqueness of this hostile environment in terms of light, salinity, pressure, space, gave birth to original organisms and bioactive substances, many of which exhibit characteristics not found in the terrestrial environment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review reported that researchers have isolated approximately 7000 marine natural compounds, 25% of which are derived from algae, 33% from sponges, 18% from coelenterates, and 24% from other invertebrate phyla . Recent reviews recorded the identification of more than 28 000 marine compounds, of which at least 3000 exhibit bioactive properties, and hundreds of new compounds being discovered each year . Few of them have been marketed or are under development, for various reasons including cost, time, and difficulties in harvesting the organism, low concentrations of natural compounds in producing organism, high toxicity of certain compounds, ecological issues, or insufficient investment by laboratories .…”
Section: Introductionmentioning
confidence: 99%
“…Marine animals have been known to produce myriad of secondary metabolites (or natural products) with diverse chemical structures and an array biological properties [1,2]. Studies of the chemical properties of these secondary metabolites have led to discovery of lead compounds some of which have entered clinical trials, particularly as anticancer and antimicrobial agents [3].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the polysaccharides from cyanobacteria used in personal skin care products and extracts of Chlorella sp. which contain oligopeptides that can promote firmness of the skin [9]. In the pharmaceutical industries drug candidates with anti-inflammatory, anticancer, and anti-infective activities have been identified [10].…”
Section: Introductionmentioning
confidence: 99%